Kedahans' wishes for their beloved Ruler - Sunday, Star (Sunday Star, 2017)
HIS Royal Highness Tuanku Abdul Halim is held in high regard by Kedahans from near and far.Here, some of the people speak about their respect for their Sultan and wish him a Happy 89th Birthday.